2013
DOI: 10.1016/j.bmcl.2012.11.035
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel arylpiperazine scaffold for fatty acid amide hydrolase inhibition with improved drug disposition properties

Abstract: We herein describe the systematic approach used to develop new analogues of compound 2, recently identified as a potent and selective fatty acid amide hydrolase (FAAH) inhibitor. Aiming at identifying new scaffolds endowed with improved drug disposition properties with respect to the phenylpyrrole-based lead, we subjected it to two different structural modification strategies. This process allowed the identification of derivatives 4b and 5c as potent, reversible and non-competitive FAAH inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…Moreover, in vivo studies evidenced its robust analgesic activity in mouse models of thermal hyperalgesia and neuropathic pain [129] . Recently, Brindisi and co‐workers disclosed novel FAAH inhibitors [130,131,132,133] . Among them, tricyclic compound 22 (IC 50 =83.5 nM on r FAAH, Figure 5) behaved as potent and selective FAAH inhibitor.…”
Section: Faah Inhibitors In Msmentioning
confidence: 99%
“…Moreover, in vivo studies evidenced its robust analgesic activity in mouse models of thermal hyperalgesia and neuropathic pain [129] . Recently, Brindisi and co‐workers disclosed novel FAAH inhibitors [130,131,132,133] . Among them, tricyclic compound 22 (IC 50 =83.5 nM on r FAAH, Figure 5) behaved as potent and selective FAAH inhibitor.…”
Section: Faah Inhibitors In Msmentioning
confidence: 99%
“…These findings suggested that the modulation of ECS may have a profound impact on AD. ECS can be modulated either by direct stimulation of CBRs or by inhibition of the ECB catabolic enzymes, leading to increased levels of ECBs [100][101][102][103][104]. For this latter purpose, Montanari et al have recently proposed some compounds, here represented by 39 (Figure 13), endowed with inhibitory 13 BioMed Research International activity towards FAAH, AChE, and BuChE [105].…”
Section: The Effects Of Dual Che Inhibitors and Modulators Of Thementioning
confidence: 99%
“…Of these, roles in fatty acid amide inactivation [31]. Hence, FAAHI blockers are also developed as one of the efficient cancer therapies so that CB1 signal transduction may happen uninterrupted to kill cancerous cells [19,32,33]. In addition, we also reviewed all plausible signal transduction pathways that could relate CB1 stimulation to cancer cell death.…”
Section: Introductionmentioning
confidence: 99%